Numerical Analysis of the Effect of Different Internal Structures on Gas-Liquid Cylindrical Cyclone Vortices and Velocities - Ling Yu; Yi Li; Haigang Wang (International Journal of Chemical Engineering)
This research uses numerical simulations to analyze the vortices and velocities inside gas-liquid separators of various shapes in order to investigate their separation. The gas-liquid flow inside the separator is simulated using the Eulerian and RNG k-ε models, which also provide iso-vorticity surfaces based on the Ω approach. The findings indicate that more powerful turbulence effects are caused by larger vortex surfaces, such as mixed structure (CS) separators, more vortex volume, and a substantially higher density of vortex nuclei. The liquid film extraction structure (LFES) separator has a larger tangential velocity at high cross sections, which is favorable for reducing film build-up. Because of its high positive radial velocity, the filter structure (FS) separator helps to lessen droplet carryover. At high cross sections, the tangential velocity of the LFES separator is higher, which is advantageous for lowering droplet carryover. The pressure and phase volume fraction distributions are consistent with the results of the vorticity and velocity analyses. When comparing the liquid separation efficiencies of separators with various designs, the FS separator outperforms the LFES separator, with the CS separator having the best efficiency. The study’s conclusions offer guidance for the separator’s structural modifications and industrial uses.